Principlism in bioethics: features and possible limitations - Boychenko, Nataliia (Filosofiya osvity. Philosophy of Education, 2023)
Advantages and disadvantages of one of the most influential methodological approaches in bioethics – principlism – are considered. The practical origins of principlism in bioethics and its theoretical origins in the philosophy of principles are revealed. The main philosophical sources of bioethics are indicated, which include utilitarianism, Kantian ethics, rule-based theory of general morality, virtue ethics, and feminist ethics. The irreducibility of principlism to any of these theories in particular and at the same time its appeal to each of them was revealed. In medical ethics, principlism appears primarily as an important practical approach that allows instrumentalization of decision-making in ethically complex situations of treating patients, conducting biomedical and clinical research. The sources of the original four principles, which are recognized by the majority of theorists of principlism, have been clarified. Among such sources, the so-called Belmont report, which names three principles, is of secondary but big importance: the principle of respect for the individual; the principle of beneficence and the principle of justice. The main arguments, classical formulation and typical contexts of application of the four principles of bioethics presented by Tom Beaucamp and James Childress as the generally accepted basis of principlism are presented: respect for autonomy, nonmaleficence, beneficence and justice. European bioethicists subsequently complement and develop these four principles with other principles: dignity, integrity and vulnerability. The main directions of criticism of principlism are revealed: lack of specificity, uncertainty of practical application of ethical theory, possible contradiction between principles. The need for constant and systematic practice of applying ethical principles in making medical decisions is defined as an antidote to these shortcomings of principlism. It is noted that Beaucamp and Childress see such permanent practice through specification and balancing procedures.